Pengaruh Kemudahan Penggunaan dan Pemasaran Digital terhadap Loyalitas Pelanggan pada Platform E-Commerce Shopee - Ihsan Ahmad Alkamal; Isyana Rahayu (Journal Economic Management and Business, 2026)
This research aims to analyze the influence of ease of use and digital marketing on customer loyalty among Shopee users, specifically students of Universitas Cipasung Class of 2022. The research employs a quantitative approach with a descriptive-causal design. Data were collected via closed questionnaires from 85 respondents selected through purposive sampling. Data analysis techniques included classical assumption tests and multiple linear regression using SPSS. The results of the t-test indicate that Ease of Use has a positive but non-significant effect on Customer Loyalty (sig. 0.725 > 0.05). Conversely, Digital Marketing has a positive and significant impact on Customer Loyalty (sig. 0.000 < 0.05). Simultaneously, both variables significantly influence loyalty with an R-Square value of 0.497, meaning 49.7% of customer loyalty is explained by these variables.